COLLABORATIVE TEACHING: PERSPECTIVES, POSSIBILITIES, AND CONTRIBUTIONS TO THE INCLUSION OF STUDENTS WITH AUTISM SPECTRUM DISORDER - da Conceição, Maria Rosa da Luz Lopes; Silva, Caroline Gisele Santos; da Silva Júnior, Vivaldo Gomes; Tork, Scheivla Suanne de Andrade Rodrigues; Pereira, Noely Corrêa Souza; Neves, Maria Gorete Vilhena; Corrêa, Cristina Picanço de Sousa; Rabelo, Janiele da Silva Melo (Seven Editora, 2026)
Considering the advancements in inclusive education policies and the significant growth in enrollment of students with Autism Spectrum Disorder (ASD) in basic education, challenges persist regarding the effective implementation of collaborative pedagogical practices between the regular classroom teacher and the special education teacher, justifying this study. The research aimed to analyze, through a literature review, the perspectives, possibilities, and contributions of collaborative teaching to the inclusion of students with ASD in basic education. To this end, a qualitative research study was conducted, specifically a bibliographic review, analyzing national and international scientific publications selected from the Scielo, Google Scholar, and CAPES Periodicals Portal databases, using descriptors related to inclusive education, collaborative teaching, and ASD. Thus, it is observed that collaborative teaching is configured as a relevant pedagogical strategy for improving the teaching and learning process, favoring the participation, academic and social development of students with ASD, in addition to promoting teacher co-responsibility and the articulation between mainstream education and Specialized Educational Services. This leads to the conclusion that the effectiveness of collaborative teaching depends on institutional conditions, collective planning, ongoing teacher training, and the integration of pedagogical practices into the school’s Political-Pedagogical Project. DOI: https://doi.org/10.56238/sevened2026.008-007